1976
DOI: 10.3171/jns.1976.44.5.0567
|View full text |Cite
|
Sign up to set email alerts
|

Infections complicating the use of external ventriculostomy

Abstract: The use of external ventriculostomy at our institution has been retrospectively analyzed to determine the incidence of cerebrospinal fluid sepsis. Placement of 65 ventriculostomies over a 2-year period resulted in three cases of complicating meningitis and ventriculitis (4.5%). Duration of ventriculostomy placement did not seem related to the rate of infection but the method of placement, the prophylactic antibiotics used, and the monitoring and collecting system employed may be important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0
5

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(56 citation statements)
references
References 4 publications
1
49
0
5
Order By: Relevance
“…A longer duration of drain placement appears to increase the risk. Three studies have shown that the risk of infection does increase with catheter duration [47,56,166]. This was also confirmed in another review that demonstrated that longer duration of external ventricular CSF drain placement increased the risk of infection [189], although the risk may plateau over time.…”
Section: Elective Fixed Interval Revisionmentioning
confidence: 48%
“…A longer duration of drain placement appears to increase the risk. Three studies have shown that the risk of infection does increase with catheter duration [47,56,166]. This was also confirmed in another review that demonstrated that longer duration of external ventricular CSF drain placement increased the risk of infection [189], although the risk may plateau over time.…”
Section: Elective Fixed Interval Revisionmentioning
confidence: 48%
“…Hemorrhagic CSF, extended duration of ventriculostomy, catheter manipulation and previous craniotomy, as well as many other factors, have been proven to increase the rate of infections [1][2][3][4][5]. We have observed in our ICU patients that those with pure ICP monitors without temporary drainage are infected more frequently and sooner than those for whom CSF drainage is maintained at least temporarily.…”
mentioning
confidence: 50%
“…Smith and Alksne [5] suggested that the use of the ventriculostomy as an EVD rather than an ICP monitor may predispose the patient to CSF infection. However, Schultz et al [4] and Mayhall et al [3] found no such association between CSF drainage and an increased risk of infection.…”
mentioning
confidence: 99%
“…The main disadvantage is the dysfunction of the optical fiber (9-40%). The hemorrhagic complication is observed in 2.8% of the cases, and the incidence of bacterial colonization has been brought down to 0-14% of the cases [5][6][7] . In a prospective study of intraparenchymal monitoring, haemorrhage was observed in 2.1% of patients without alteration of the coagulation, and in 15.3% of their counterparts with coagulopathy 8 .…”
Section: Discussionmentioning
confidence: 99%